The effect of service quality on Indosat product sales level at the Deliz Cell outlet - Ahmad Rojikun (Privietlab, 2021)
Analysis of Service Quality on Indosat Product Sales Level at Deliz Cell Outlets. This research is qualitative in nature, where in this study the focus of research is the community who uses Indosat products. In this study the authors use a descriptive problem formulation, where the researcher explores what is the basis and causes and social situations that occur in society towards loyalty using Indosat products. People who use Indosat products, their information or testimony is taken at one of the pulse outlets in the area of ​​Jalan Setiabudi, Pamulang Timur with the brand Deliz Cell, and at the same time the outlet represents the data source or the resource person in this study including the researchers themselves. From the results of qualitative research conducted by Rıanti, it is hoped that the author will get a bright spot and clarity on the real problems that occur in the social environment of Indosat product users who are loyal to the Indosat brand, and it is hoped that later they will get a concrete picture of why people tend to use Indosat products in particular. in the area of ​​East Pamulang and its surroundings, more specifically, customers who shop at Deliz Cell outlets.